Simultaneous Approximation for Generalized Srivastava-Gupta Operators. (6th April 2015) - Acar, Tuncer; Mishra, Lakshmi Narayan; Mishra, Vishnu Narayan
Abstract : We introduce a new Stancu type generalization of Srivastava-Gupta operators to approximate integrable functions on the interval0, ∞ and estimate the rate of convergence for functions having derivatives of bounded variation. Also we present simultenaous approximation by new operators in the end of the paper.